Polymer nanocomposite membranes for oil/water emulsion - Md Abdul Majed, Patwary; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri; Faisal Islam, Chowdhury; Md. Zahidul, Islam (Woodhead Publishing is an imprint of Elsevier, 2025)
Oil-contaminated wastewater is widely acknowledged as a significant global source of pollution. This type of wastewater originates from several sources, including crude oil extraction, oil refining, the petrochemical sector, compressor condensates, metal treating, vehicle cleaning, and lubricants and cooling agents. The occurrence of the oil leak on Deepwater Horizon in 2010 exposed the challenges associated with achieving efficient separation of oil and water using current skills. Oily wastewater is classified as a hazardous form of industrial wastewater due to the inclusion of toxic compounds such as phenols, petroleum, and polyaromatic hydrocarbons. These substances are known to hinder the growth of plants, and animals and also present hazards of mutagenicity and carcinogenicity to people. Pollutants like hydrocarbon compounds primarily originate from industrial effluent. Oil/water (O/W) emulsions are the most common form of this effluent. The size of the particles determines whether they are microemulsions or nanoemulsions. Nanoemulsions have exceptional stability, making them highly resistant to destabilization. This type of pollutant is hazardous and results in numerous health issues. Hence, it is crucial to separate O/W emulsions, particularly those that are stable (with droplet sizes smaller than 0.1 µm).